Correlation Between Recombination Dynamics and Quantum Barrier Thickness in InGaN-Based Micro-LEDs - Mengyue Mo; Ying Jiang; Penggang Li; Zhiqiang Liu; Xu Yang; Weifang Lu; Jinchai Li; Kai Huang; Junyong Kang; Rong Zhang (IEEE Photonics Journal)
To tackle the efficiency droop, we employed an epitaxial structure engineering approach and utilized SimuLED software to thoroughly investigate the influence of the quantum barrier (QB) thickness on the performance of Micro-LEDs, and delve into the corresponding carrier transport behavior. The results demonstrate that the effect of QB thickness on the performance of Micro-LEDs is closely related to injection current density. Within the current density range of 0–30 A/cm2, a thicker QB layer leads to a higher internal quantum efficiency (IQE) for Micro-LEDs. Conversely, when the current density is in the range of 30–100 A/cm2, employing a thinner QB layer in the LED structure can yield higher IQE values. In addition, this work suggests that tunneling effects and Quantum Confined Stark Effect (QCSE) dominate at different current densities, resulting in an opposite dependency of IQE on QB thickness. Furthermore, our findings indicate that adjusting QB thickness can significantly affect both the peak external quantum efficiency (EQE) and peak current density of Micro-LEDs.